Domestic food hygiene practices among households in Pulipakkam Village, Kanchipuram District: a cross- sectional study - N., Lakshmi; R., Ramya M.; Felicia, J. Princy (International Journal Of Community Medicine And Public Health, 2020)
Background: Food hygiene implies measures necessary to ensure safety of food from production to consumption. Food can become contaminated at any point during harvesting, processing, storage, distribution, transportation and preparation. Lack of proper food hygiene can lead to food borne diseases and death of the consumers. The purpose of food hygiene is to prepare and provide safe food and consequently contribute to a healthy and protective society. Methods: A community based cross-sectional study was conducted from September 2019 to February 2020 among 81 household food-handlers in a rural area of Kanchipuram district. A pre-tested semi-structured questionnaire based on WHO (World Health Organization) Food Safety Manual was used to collect the data regarding kitchen and food hygiene practices. Results: The study revealed that 74%of respondents handle drinking water unsatisfactorily. 89% of people don’t store cooked food in the refrigerator within 2 hours and nearly 54% of them don’t boil water before drinking. Only 48% of them separated raw food from cooked food. Conclusions: The results of the study showed that food hygiene practices should be improved in the community to safe guard them against food-borne diseases.